PENGARUH MOTIVASI HEDONIS DAN ATMOSFER TOKO TERHADAP PEMBELIAN IMPULSIF PADA REMAJA PUTRI DI DENPASAR - Ratih, Ida Ayu Tryastiti; Astiti, Dewi Puri (Jurnal Psikologi Udayana; Vol 3 No 2 (2016)DO - 10.24843/JPU.2016.v03.i02.p04, 2016)
lmpulse buying is other type from consumer buying model which is done spontaneously, in which it is happened when the consumer suddenly have a strong desire to buy something fast and ignore all consideration of the consequences. The act of impulse buying mostly happened on nowadays adolescent, in which their existence in order to be claimed in their social environment by following the new trend in their community. This research is aimed to show the influence of hedonic motive and store atmosphere towards the impulse buying on the adolescence girls. The population of the research is female students at Denpasar by using incidental sampling technique. The measuring instrument used in the research is the scale of hedonic motive, store atmosphere, and impulse buying. The result of multiple regression analysis shows that hedonic motive and store atmosphere are 42,8% simultaneously influential towards impulse buying on the adolescence girls at Denpasar. The result of standardized beta coefficient of hedonic motive and store atmosphere shows that the hedonic motive and store atmosphere is significantly influential towards the impulse buying. Keywords : hedonic motive, store atmosphere, impulse buying, adolescent girls